Pengaruh Rasio Bahan Baku Dan Variasi Ukuran Partikel Terhadap Nilai Kalor Biobriket Hasil Pemanfaatan Limbah Tandan Kosong Sawit Dan Lumpur IPAL Produksi Minyak Sawit - Hafizh, Muhammad; Yenie, Elvi; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
WWTP sludge in palm oil production with the addition of empty fruit bunch can be used as raw material for making briquettes through the carbonization process. This study aims to study the effect of variations in treatment on the calorific value and compressive strength of the briquettes produced. In this study the WWTP sludge in palm oil production was carbonated at 300Â°C for 60 minutes and empty fruit bunch at 450Â°C for 90 minutes. Variations of variables used were particle size -80/+100, -100/+120, and -120/+140 mesh and the composition of empty fruit bunch and WWTP sludge in palm oil production were 90%:10%, 80%:20%, 70%:30%, and 60%:40%. The results showed that the best briquette heating value were obtained on the composition of raw materials 90%:10% with a particle size of -80/+100 mesh were the heating value of 5310,46 cal/gr and the best compressive strength were obtained on the composition of raw materials 90%:10% with a particle size of -120/+140.Keywords: briquettes, crude gliserol, calorific value